Phytochemical analysis and antimicrobial and antifungal potential of extracts and fractions of Poincianella bracteosa - Santana, Letícia Gonçalves Aguiar; Passos, Marcel Mark da Silva; Fernandes, Erica Porto; Silva, Patrick dos Santos; Gualberto, Simone Andrade; de Carvalho, Silmara Almeida (Eclética Química, 2026)
The Caatinga is a Brazilian biome with great plant diversity and significant economic and pharmacological potential. It is a valuable source of medicinal resources, with many species used in folk medicine. The study on Poincianella bracteosa highlighted its medicinal properties, such as anti-inflammatory and antimicrobial action. The antimicrobial activities of crude extracts and fractions obtained from different plant parts were evaluated against pathogenic microorganisms. The extracts were obtained through exhaustive percolation with a 70% hydroethanolic solution and fractionated using solvents of lower polarity, resulting in hexane, dichloromethane, and ethyl acetate fractions. The fractions showed greater effectiveness than the crude extracts, with the dichloromethane fraction from the root exhibiting the highest inhibitory activity, with a minimum inhibitory concentration of 0.03 mg/mL against Enterococcus faecalis, Staphylococcus aureus, and Pseudomonas aeruginosa. These results indicate the antibacterial potential of Poincianella bracteosa.